Development of a bead-based Luminex assay using lipopolysaccharide specific monoclonal antibodies to detect biological threats from Brucella species. Issue 1 (December 2015) - Silbereisen, Angelika; Tamborrini, Marco; Wittwer, Matthias; Schürch, Nadia; Pluschke, Gerd
Abstract Background Brucella, a Gram-negative bacterium, is classified as a potential bioterrorism agent mainly due to the low dose needed to cause infection and the ability to transmit the bacteria via aerosols. Goats/sheep, cattle, pigs, dogs, sheep and rodents are infected byB. melitensis, B. abortus, B. suis, B. canis, B. ovis andB. neotomae, respectively, the six classicalBrucella species. Most human cases are caused byB. melitensis andB. abortus . Our aim was to specifically detectBrucellae with 'smooth' lipopolysaccharide (LPS) using a highly sensitive monoclonal antibody (mAb) based immunological assay. Methods To complement molecular detection systems for potential bioterror agents, as required by international biodefense regulations, sets of mAbs were generated by B cell hybridoma technology and used to develop immunological assays. The combination of mAbs most suitable for an antigen capture assay format was identified and an immunoassay using the Luminex xMAP technology was developed. Results MAbs specific for the LPS O-antigen ofBrucella spp . were generated by immunising mice with inactivatedB. melitensis orB. abortus cells. Most mAbs recognised bothB. melitensis andB. abortus and antigen binding was not impeded by inactivation of the bacterial cells by γ irradiation, formalin or heat treatment, a step required to analyse the samples immunologically under biosafety level two conditions. The Luminex assay recognised all testedBrucella species with 'smooth' LPS with detection limits of 2 × 102 to 8 × 104 cells per mL, depending on the species tested. Milk samples spiked withBrucella spp. cells were identified successfully using the Luminex assay. In addition, the bead-based immunoassay was integrated into a multiplex format, allowing for simultaneous, rapid and specific detection ofBrucella spp., Bacillus anthracis, Francisella tularensis andYersinia pestis within a single sample. Conclusion Overall, the robust Luminex assay should allow detection ofBrucella spp. in both natural outbreak and bio-threat situations.